Has globalisation really peaked for Europe? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2022)
This paper builds on the recent arguments put forward by Richard Baldwin and others debunking the myth that we enter a period of de-globalisation. The paper argues that globalisation is a complex phenomenon that requires detailed, firm-level indicators going beyond simple aggregate metrics. When using such indicators, the picture is much more nuanced and, in the case of Europe, the role of global trade is as important as ever for hundreds of thousands of companies and millions of jobs supported by global trade flows. A strong participation in the "new globalisation" is also key for the future EU competitiveness in technology-driven sectors.
Keywords: 330; Globalisierung; Internationale Wirtschaft; EU-Staaten; Welt